Principles, Utility and Limitations of Pulse Oximetry in Management of COVID-19 - Joshi, Lok Raj (Journal of Lumbini Medical College, 2020)
Pulse oximetry is an essential component of the standard care of COVID-19 patients. In the context of the spreading COVID-19 pandemic for which no targeted therapy or vaccines are yet available, early identification of the severe cases or cases with high risk of severe disease and appropriate supportive treatment are of paramount importance to save lives. Pulse oximetry is a cheap, fast, easy to use, noninvasive, painless and accurate tool that allows real-time monitoring of hypoxemia. As the primary target of the disease is the respiratory system pulse oximetry provides an unparalleled way to assess the severity of the disease, guide supportive therapies and monitor the clinical status and response to treatment with greater benefits in the low-resource settings. All settings from the quarantine facilities at the ground level to the ICUs in the highest level hospitals can utilize it to achieve their goals. To get the best of this tool, it needs to be used properly and the findings interpreted carefully. Role of basic understanding of the physiological principles and technology behind its use and awareness of its limitations cannot be overemphasized. The pulse oximetry readings are interpreted in the context of blood hemoglobin concentration, tissue perfusion, arterial blood carbon dioxide concentration and oxygen supplementation status.